Design of Bitterless Atenolol Prodrugs for the Use in Aqueous Formulations for Pediatrics and Geriatrics - Rafik Karaman; Alaa Qtait (Technological Innovation in Pharmaceutical Research Vol. 4, 2021)
Based on DFT, MP2, and hybrid GGA: MPW1k calculations for an acid-catalyzed hydrolysis of nine Kirby’s N-alkylmaleamic acids, a number of atenolol prodrugs were designed. A linear correlation of the calculated and experimental rate values for the nine Kirby’s N-alkylmaleamic acids has established credible basis for designing atenolol prodrugs that are bitterless, are stable in neutral aqueous solutions, and have the potential to release the parent drug in a sustained release manner. For example, based on the calculated B3LYP/6-31 G (d,p) rates, the predicted t1/2 values for atenolol prodrugs ProD 1-ProD 2 at pH 2 were 65.3 hours and 11.8 minutes, respectively. In vitro kinetic study of atenolol prodrug ProD 1 revealed that the t1/2 was largely affected by the pH of the medium. The determined t1/2 values in 1N HCl, buffer pH 2, and buffer pH 5 were 2.53, 3.82, and 133 hours, respectively.